Comparative effectiveness of metronidazole and vancomycin for treatment of Clostridioides difficile infection in hospitalized children - Thomas J. Sandora; Timothy J. Savage; Morgan E. Ryan; Suzanne E. Dahlberg; Kaitlyn Daugherty; Ciarán P. Kelly; Nira R. Pollock; Larry K. Kociolek (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract